How the characteristics of pediatric neurologists in Latin America influence the communication of sudden unexpected death in epilepsy to patients and caregivers - Viviana Venegas; Carla Manterola; Jose De Pablo; Mariano Garcia; Sonia Ponce de León; Gabriel Cavada (My University, 2022)
AbstractObjectiveThis study aimed to describe the characteristics of pediatric neurologists (PNs) in Latin America (LA) who attend to children and adolescents with epilepsy and convey to them the risk of sudden unexpected death in epilepsy (SUDEP).MethodsPersonal data and details of discussion of SUDEP with families, including relevance of SUDEP disclosure, frequency of such communication, perceived benefits and risks of disclosure, extent of training received on such disclosure, and professional experience with SUDEP, were collected through an online survey of PNs from LA. Their personal experience in carrying out this conversation was obtained through responses to an open question, further used to identify the main barriers.ResultsOf the 442 surveys received, 367 (83%) were analyzed. Most participants (73.8%) responded that the communication of SUDEP risk was relevant or very relevant; however, only 17.9% reported communicating it always or very frequently. Factors that increased the frequency of SUDEP communication included patients with higher levels of complexity (OR = 2.18, P = .003) and the physician's personal experience with SUDEP (OR = 2.305, P < .001). Direct questions from the family and avoiding scaring them about a rare outcome were the main motivations behind discussing and not discussing SUDEP, respectively. In the open question, respondents identified worries about the patient's ability to understand the information and cultural gaps as barriers. “Informing with the intention of improving adherence to treatment” and “establishing an empathic relationship” were significantly related. Further, the concept of “do not scare” was significantly related to “personal difficulties in discussing SUDEP.”SignificanceAlthough most PNs agree that communication about SUDEP is relevant, only a minority actually engages in it. Participants identified a lack of appropriate training in such communication as a barrier. A better understanding of communication expectations, education of health professionals, and communication techniques have a strong relevance in diminishing the gap between guidelines and practice.
Keywords: risk-factors report; implementation subcommittee; guideline development; unexplained death; sudep disclosure; incidence rates; mortality; dissemination; definitions; mechanisms